Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera) - Yan, Chuncai; Song, Chao; Liu, Ting; Zhao, Guangjun; Hou, Ziyuan; Cao, Wei; Wang, Xinhua (Zootaxa, 2017)
Polypedilum (Tripodura) enshiense Song & Wang sp. n. and P. (Tripodura) jianfengense Song & Wang sp. n. are described and illustrated as male imagines from China. P. (Uresipedilum) paraconvictum Yamamoto, Yamamoto & Hirowatari, 2016 is recorded from China for the first time. Cytochrome coxidase subunit I (COI) sequence of above species are uploaded to Barcode of Life Data Systems (BOLD).